Aristotle: on the expression “amicably make common use” (2021)
In the framework of discussions on common goods, the common elements, or urban common and their practices, I propose going back to Aristotle, in order to examine his considerations on what he calls “common,” besides the expression “amicably make common use,” used in Politics to refer to the practice that citizens need to undertake in relation to said assets. The aim is to specify their contributions and extract others that may be derived from their reflections and that may enrich the current discussions on this topic.